4.5x-13.5=0

Simple and best practice solution for 4.5x-13.5=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4.5x-13.5=0 equation:


Simplifying
4.5x + -13.5 = 0

Reorder the terms:
-13.5 + 4.5x = 0

Solving
-13.5 + 4.5x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '13.5' to each side of the equation.
-13.5 + 13.5 + 4.5x = 0 + 13.5

Combine like terms: -13.5 + 13.5 = 0.0
0.0 + 4.5x = 0 + 13.5
4.5x = 0 + 13.5

Combine like terms: 0 + 13.5 = 13.5
4.5x = 13.5

Divide each side by '4.5'.
x = 3

Simplifying
x = 3

See similar equations:

| (X^2-13)*(14-X)= | | (4j-5k)*(5i+5j+7k)=equation | | 3(4-5x/7)=(2x/5)-8 | | 0.5t^2-31t+500=0 | | 3x-12+(3x)+9=0 | | 2.3x+4.6=0 | | 22x^4-5x^3+19x-5x-3=0 | | X^3-2x-2=0 | | 2+3x+-2x^2=0 | | 3x+1=-3x+8 | | -8j/3=9 | | 24=23 | | 2h^5-3h^2+h^3=-1h^6 | | 2.5+10=0 | | -(-2x)=(-20) | | 2*x+1=(2*x+1)*(x-1) | | -148-10x=108-31x | | -4(0)+6(y)-5(0)=60 | | -4(0)+6(y)-5(z)=60 | | -4(x)+6(0)-5(0)=60 | | y=0.2(x-2)(x+1)(x-5) | | 2x+3(0)-6(0)= | | (2/x-12)(-5x-5) | | 2x-26=5x+10 | | x^2+4x+11=(2x+3)sqrt(x^2+9) | | f(x)=(x-3)(x+2)(x+5) | | X-3.75=0.6 | | x+19=3x+10 | | 3a+5=2a+10 | | x^2+y^2-10x+8y+41=0 | | 4x^2+4y^2-8x-16y-29=0 | | x-x(0.20)=175 |

Equations solver categories